The effect of hydrophilic and hydrophobic polymers on release profiles of diclofenac sodium from matrix tablets - Md Imamul Islam; Md Kamal Hossain; Taksim Ahmed; Prabhat Bhusal; Md Sohel Rana; Tanveer A Khan (Archives of Global Professionals, 2013)
Objective: The current study aimed to develop a matrix type sustained release Diclofenac tablet, using hydrophilic hydroxypropyl methylcellulose (HPMC) and hydrophobic polymer cetyl alcohol (CA). Materials and Methods: Two different polymers, that is, Methocel K15MCR® and CA were used in various proportions as release controlling factor. Matrix tablets were prepared by wet granulation technique. The physicochemical properties of the granules and tablets were evaluated. In vitro dissolution studies of prepared matrix tablet and patent product Voltaren SR® tablet (VSR) were performed at pH 7.4 phosphate buffer at 100 rpm, and at 37 ± 0.5°C, and subjected to in vitro bioequivalence study in terms of similarity and difference factors. Stability studies were conducted for 6 months using optimized formulation for extended period of time, both at room temperature and accelerated conditions. The dissolution data were fit to Zero-order, First-order, Higuchi, and Korsmeyer-Peppas' equations. Results: The formulated tablets showed acceptable weight variation, hardness, drug content uniformity with sustained release matrix characteristics. Hydrophilic Methocel K15 MCR® matrices-based tablets showed zero-order and hydrophobic CA matrices-based tablets followed first-order kinetics except for formulation six (F6 showed zero-order profile). It was found that formulations containing CA showed better dissolution properties with respect to formulations containing Methocel K15 MCR® in terms of similarity and difference factor. Furthermore, the formulations F4, F5, and F6 exhibited similar drug release profile as compared with VSR tablet, which indicated that these formulations could be bioequivalent with VSR tablet in vitro. Tablets were stable both at room temperature and as well as at accelerated conditions. Conclusion: The present study demonstrated that Diclofenac could be successfully prepared using an appropriate amount of Methocel K15 MCR® and CA in the form of matrix tablets with similar dissolution profile of patent product Voltaren SR® . The type of polymers used was found to induce a profound effect on release rate and mechanism.